2022
DOI: 10.3389/fgene.2022.917454
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circRNA–miRNA–mRNA Regulatory Network and Crucial Signaling Pathway Axis Involved in Tetralogy of Fallot

Abstract: Tetralogy of Fallot (TOF) is one of the most common cyanotic congenital heart diseases (CHD) worldwide; however, its pathogenesis remains unclear. Recent studies have shown that circular RNAs (circRNAs) act as “sponges” for microRNAs (miRNAs) to compete for endogenous RNA (ceRNA) and play important roles in regulating gene transcription and biological processes. However, the mechanism of ceRNA in TOF remains unclear. To explore the crucial regulatory connections and pathways of TOF, we obtained the human TOF g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The data support the idea that the CHD patients’ illness state is caused by a changed miRNA expression. In another study, it was revealed that hsa-miR-148a and BCL2L11 are linked to cardiomyocyte apoptosis and Hsa-miR-148a might affect BCL2L11 [ 240 ]. Recent findings have shown that miR-153-3p targets βII spectrin, which has a negative effect on myocardial development [ 241 ].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…The data support the idea that the CHD patients’ illness state is caused by a changed miRNA expression. In another study, it was revealed that hsa-miR-148a and BCL2L11 are linked to cardiomyocyte apoptosis and Hsa-miR-148a might affect BCL2L11 [ 240 ]. Recent findings have shown that miR-153-3p targets βII spectrin, which has a negative effect on myocardial development [ 241 ].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…A recent study aimed to generate a circRNA-miRNA-mRNA network in TOF. They analyzed three datasets available in GEO databases comparing profiles and identified 29 miRNA, 13 circRNAs and 88 mRNAs ( 138 ). Interestingly, a comparison between overlapping miRNA profiles in four other studies yielded two miRNAs that were identified in all 4 studies and 5 miRNAs that were identified in at least 3 of the 4 studies ( Table 1 ) ( 139 142 ).…”
Section: Is There a Molecular Signature In The Right Ventricle Of Tet...mentioning
confidence: 99%
“…Interestingly, a comparison between overlapping miRNA profiles in four other studies yielded two miRNAs that were identified in all 4 studies and 5 miRNAs that were identified in at least 3 of the 4 studies (Table 1) (139-142). MiR-222, also identified in the network by Kan et al has been associated with exercise-induced myocardial adaptation, atrial fibrillation, is involved in function of L-type calcium channels and is a target of angiogenesis and proliferation via ERBB4 and HIF1α (138,(143)(144)(145)(146). MiR-194 has been linked to the p53 pathway and may be involved in pulmonary angiogenesis (147).…”
Section: Is There a Molecular Signature In The Right Ventricle Of Tet...mentioning
confidence: 99%
“…), and epigenetic modi cations based on gene methylation (e.g., methylation of LINE1, NKX2-5, ZFPM2, etc.) [5][6][7][8][9]. The environmental factors include physical factors (such as ionizing radiation and noise pollution), chemical factors (such as long-term exposure to organic solvents, cocaine, etc.…”
Section: Introductionmentioning
confidence: 99%